Ռուդոլֆ Վիրխովը և Հայաստանը - Վարդանյան, Ստելլա («Նաիրի» հրատ.)
В статье приведены материалы, посвященные малоизученным страницам биографии великого немецкого врача Рудольфа Вирхова (1821-1902), основоположника патологической анатомии и создателя теории целлюлярной патологии в современной медицине. Исследование последнего периода жизни Вирхова, связанного с Кавказскими экспедициями и археологическими раскопками на территории Армянского нагорья, проливают новый свет на его глубокое понимание роли Армении в истории мировой культуры и выявляют его связи с крупными армянскими учеными и врачами XIX-XX вв. The article embraces materials elucidating some unknown pages in the biography of great German physician Rudolf Virchow (1821-1902), the founder of pathological anatomy and creator of cellular theory in modern medicine. The study deals with the last period of Virchow‟s life and his work associated with the Caucasian expedition and excavations on the territory of the Armenian Highland, which shed a new light on Virchow's profound understanding of Armenia‟s role in the history of world culture and reveal his connections with some eminent representatives of Armenian science and medicine in XIX-XX centuries.
Keywords: Գիտություն; Պատմություն; Կենսագրություն